KEMAMPUAN MENGGUNAKAN KALIMAT EFEKTIF DALAM KARANGAN ARGUMENTASI SISWA KELAS X SMA NEGERI 1 SOSOPAN - toras barita bayo (Jurnal Education and Development, 2019)
This study discusses the problem of effective sentences in the essay of argumentation for class X students of Sosopan 1 Public High School. The aim is to see the students 'ability to write by paying attention to the aspects of economics and the use of spelling that is perfected in students' essays. To be able to draw conclusions in this study, the authors formulated a research problem namely "How is the ability to use effective sentences in terms of savings and the use of spelling that is perfected in the essay of argumentation in class X of Sosopan 1 Public High School. Effective sentences are sentences that can express ideas, thoughts and feelings appropriately. Effective sentences must be colored by good and correct use of enhanced spelling (EYD). Savings referred to here are those sentences that avoid redundant words, namely repetition of the subject, the possibility of hyponym, the use of the word that is unnecessary, the use of prepositions from and rather than unnecessary, while the use of EYD is seen from writing on, to and from composition of students. This research is a descriptive study, the population in this study were students of class X SMA 1 Sosopan. Sampling was carried out by local random sampling conducted by lottery and from the lottery results, the class X3 was selected as a sample of 30 people. The object studied is the effectiveness of sentences in terms of savings and the use of enhanced spelling (EYD) in the essays of student argumentation. Analyzing sentences is done using a percentage formula, which is the number of ineffective sentences divided by the total number of sentences, then multiplied by 100%. Based on the results of data analysis, it is known that the average student's ability to use effective sentences in terms of savings and use of enhanced spelling (EYD) in students' essays is categorized as "good" (71.9% of 591 sentences). The effective sentence includes, a) the repetition of a subject consisting of 93 errors or 56% of ineffective sentences, b) the possibility of a hyponym consists of 22 errors or 13.2% of ineffective sentences, c) the use of prepositions from and than what is not needed consists of 10 errors or 6% of ineffective sentences, d) the use of conjunctions that are not needed consists of 3 errors or 1.9% of the number of ineffective sentences, e) Writing on, to and from consists of 38 or 22.9% of the number of ineffective sentences.